Relationship between selected physical fitness indicators and golf performances among elite university golfers - Muhamad, S. S. A.; Mohd, A. A.; Muhamad, N. M.; Noor, A. A. R.; Nurul, A. A. K.; Shariman, I. I.; Hosni, H. (Journal of Physical Education and Sport, 2022)
Nowadays, most golfers have incorporated physical conditioning regimes to become the best player on the field. That is why the new generation of golfers nowadays is leaner, muscular, and more flexible than the previous generation. The purpose of the current study was to investigate the relationship between physical fitness and golf performances among elite collegiate golfers at National Golf Academy, Universiti Utara Malaysia. Besides, a comparison analysis was also conducted to see which physical fitness has a significant difference between male and female elite golfers. An Independent t-test was used to seek the differences between male and female golfers on their physical fitness attributes, while a Pearson Correlation analysis was used to seek which physical fitness attributes correlates with the golf performances. Significant correlations were found between height, arm length, leg length and predicted Vo2max with the golf measures. Significant correlations were also noted between muscle power and arm strength with almost all the variables in golf measures. While the upper body performance was the only significant inversely correlated with putts per round (r=-.559, p = 0.05). When comparing the physical attributed between genders, differences between male and female golfers were found in anthropometric measures (i.e: arm length, leg length, height, mass and predicted Vo2max) and golf driver performances, golf 5-iron performances, average score and greens in regulations (p = 0.05). From the results it can be suggested that male and female elite golfers do have differences in terms of their physical fitness and their golf performances regardless being in the same elite category. Other than that, results also suggest the anthropometric data, peripheral muscle strength and cardiovascular endurance are correlated with golf performance. These results can be used in developing training programs as well as to be used for the development of talent identification programs.